Exploring Green Creativity: The Effects of Green Transformational Leadership, Green Innovation Climate, and Green Autonomy - Maitlo, Qamaruddin; Wang, Xiuting; Jingdong, Yan; Lashari, Ishfaque Ahmed; Faraz, Naveed Ahmad; Hajaro, Nazim Hussain (Frontiers in Psychology, 2022)
Because no prior published literature discusses the role of green innovation climate and green autonomy to enhance green creativity, this study aims to offer these two novel constructs. This study, using the componential theory of creativity, investigates the antecedents of green creativity, such as green transformational leadership, green innovation clime, and green autonomy. The authors employed structural equation modeling (SEM) to analyze survey-based data collected from automotive firms in China. The findings reveal that green transformational leadership directly and indirectly via green innovation climate (partial mediation) affects the green creative behavior of employees in China. Moreover, green autonomy moderates the relationship between green innovation climate and green creativity. This pivotal contribution suggests that automotive business enterprises should develop green transformational leadership to nurture green innovation climate and provide autonomy for green creative performance. The above antecedents of green creativity may enable business firms to gain competitive advantage by innovating green products and practices.